Penilaian Menu Harian dari Penghuni Panti Werdha dalam Rangka Memperbaiki Asupan dan Status Gizi Lansia: The Assessment of Daily Menus in Nursing Home Residents for Improving Intake and Nutritional Status in Elderly - Farapti Farapti; Martina Puspa Wangi; Sri Adiningsih (Amerta Nutrition, 2023)
Background: Malnutrition has impacted the health condition and life quality of the elderly who live in nursing homes. Unmaximized menu planning can cause this condition. Objectives: This study aimed to analyze the nutrition content of the menu provided by the nursing home based on recommended dietary allowance (RDA) for older people and to identify the current nutrition status of the elderly Methods: The food intakes were evaluated by observing all menus during the five days. Nutrient contents were analyzed by calculating all meal nutrition and comparing them to the recommended dietary allowance for the elderly. Body weight was measured using Bio Impedance Analysis (BIA) Tanita, and a stadiometer measured body height. Furthermore, weight and high were measured based on body mass index calculation to measure nutritional status. Results:  It was found that the mean energy content was 1242.6 ± 193.9 kcal/day, and only 69.03 ± 10.7% fulfilled the recommendation. For protein content, it only met 70.5% of the RDA. Macronutrients such as protein are only 70.5% of the recommended dietary needs for the elderly. From BMI analysis, it was found that 26.23 % of the elderly are undernutrition. Conclusions: The nutritional content of the menus served for the elderly in nursing homes did not yet meet the daily requirement and is still below that recommended for the elderly, so the nutrient of the menus should be increased to achieve optimum nutritional status.